MicroRNA‐196a promotes an oncogenic effect in head and neck cancer cells by suppressing annexin A1 and enhancing radioresistance. Issue 5 (12th January 2015) - Suh, Yae‐Eun; Raulf, Nina; Gäken, Joop; Lawler, Katherine; Urbano, Teresa Guerrero; Bullenkamp, Jessica; Gobeil, Stéphane; Huot, Jacques; Odell, Eddy; Tavassoli, Mahvash
<x xml:space="preserve">Abstract</x> Radiotherapy is a major treatment modality for head and neck squamous cell carcinoma (HNSCC). Up to 50% of patients with locally advanced disease relapse after radical treatment and there is therefore a need to develop predictive bomarkers for clinical use that allow the selection of patients who are likely to respond. MicroRNA (miRNA) expression profiling of a panel of HNSCC tumours with and without recurrent disease after surgery and radiotherapy detected miR‐196a as one of the highest upregulated miRNAs in the poor prognostic group. To further study the role of miR‐196a, its expression was determined in eight head and neck cancer cell lines. Overexpression of miR‐196a in HNSCC cells, with low endogenous miR‐196a expression, significantly increased cell proliferation, migration and invasion, and induced epithelial to mesenchymal transition. Conversely, miR‐196a knockdown in cells with high endogenous expression levels significantly reduced oncogenic behaviour. Importantly, overexpression of miR‐196a increased radioresistance of cells as measured by gamma H2AX staining and MTT survival assay. Annexin A1 (ANXA1), a known target of miR‐196a, was found to be directly modulated by miR‐196a as measured by luciferase assay and confirmed by Western blot analysis. ANXA1 knockdown in HNSCC exhibited similar phenotypic effects to miR‐196a overexpression, suggesting the oncogenic effect of miR‐196a may at least be partly regulated through suppression of ANXA1. In conclusion, this study identifies miR‐196a as a potential important biomarker of prognosis and response of HNSCC to radiotherapy. Furthermore, our data suggest that miR‐196a and/or its target gene ANXA1 could represent important therapeutic targets in HNSCC.